ANTECEDENTS OF EMPLOYEE WORK DISCIPLINE - Tehubijuluw Zacharias; Jimmy Sirait; Demsy Wattimena (JURNAL BADATI, 2023)
This study aims to determine, test and analyze the influence of the antecedent factors of leadership, supervision, work environment and commitment to employee discipline at the Lesane Village office, Masohi City, Central Maluku. This study uses a descriptive-quantitative approach with a causal correlation type. The population used in this study were all employees of the Lesane Village Office, Masohi City, Central Maluku, consisting of 27 people. The sample is part of the number and characteristics possessed by the population. The method of determining the sample is full sampling because the population is very small. Data were analyzed using multiple linear regression analysis.The results of the study concluded that the antecedents of leadership, supervision, work environment and organizational commitment had a positive and significant effect on employee discipline at the Lesane Village Office, Masohi City, Central Maluku, both partially and simultaneously.